Analysis and synthesis of robust control system with separable nonlinearities. - Neusa Maria Franco de Oliveira (2003)
The objective of this thesis is to propose a design method for controllers to secure specified robust oscillation amplitude and frequency for separable nonlinear systems exhibiting unavoidable or desirable limit cycles. The design approach of robust limit cycle controllers introduced here can be used for autonomous systems with separable single-input-single-output nonlinearities. The proposed design approach consists of quasi-linearization of the nonlinearity via the Describing Function (DF) method and then shaping the loop to reach desired limit cycle characteristics. As the DF method is used, loop shaping takes place in the Nyquist plot, because the intersection between the loop shaped loci and the DF negative reciprocal loci is related to the limit cycle characteristics of the system. In the problem addressed in this thesis, the original linear subsystem (i.e. without controller) is considered as an uncertain system with unstructured uncertainty. A condition to be satisfied by the shaped loop is given such that the controlled system has limit cycle characteristics as close as possible to the nominal characteristics even though the uncertainty considered. Three requirements are satisfied in the loop shaping step. The first requirement assures the nominal desired limit cycle characteristics in the designed system. The second is related to limit cycle stability, i.e., if a (small) perturbation disturbs the limit cycle of the controlled system, it will return to the earlier limit cycle. The third requirement addresses the robustness question, and the condition mentioned before is used. After the loop is shaped to satisfy the requirements, a controller is computed so that the controlled linear subsystem transfer function is equal the transfer function obtained in the loop shaping. This approach is applicable to systems with linear subsystems that are minimum phase. In some cases it may be necessary to add a high frequency pole in order to obtain a proper controller. Examples are given in order to illustrate the robustness of the controlled system with respect to uncertainty in the linear subsystem model. In the first example the intersection between the loop shaped loci and the DF negative reciprocal loci is on the real axis. In the second example the crossing point is not on the real axis and so, restrictions more generals than the ones used in the first example are used. In the third example the crossing point is on the real axis and output disturbance is considered.